Ultrastructural Characteristics of Mouse Preantral Follicles Isolated from Vitrified and Non Vitrified Ovaries after In Vitro Maturation - Kamran Haidari; Mojdeh Salehnia; Mojtaba Rezazadeh Valoujerdi (Cell Journal, 2007)
Objective: The purpose of the present study was to verify the ultrastructural characteristics of cultured mouse preantral follicles from fresh and vitrified –warmed ovarian tissues.Materials and Methods: The ovaries of 14-day-old mice (n = 5) were vitrified using a mixture of ethylene glycol, ficoll 70 and sucrose. The preantral follicles were isolated and cultured in α-minimum essential medium supplemented with 5% fetal bovine serum, 100 mIU/ml recombinant follicle stimulating hormone, 1% insulin, transferrin and selenium, 20ng/ml murine recombinant epidermal growth factor for four days. The follicles were fixed in 2.5% glutaraldehyde and post fixed with 1% osmium tetroxide and processed for transmission electron microscopic studies.Results: Cultured preantral follicles of the control group on day 4 consisted of an oocyte surrounded by several layers of polyhedral granulosa and flattened theca cells. The granulosa cells and oocytes were in close connection. Several granulosa cell projections could be seen in the outer layer of zona pellucida. Polyribosomes and rough endoplasmic reticulum cisternae were observed in the most samples in association with mitochondria. The ultrastructure of vitrified follicles was similar to the control. The homogenous zona pellucida surrounded the oocytes but the granulosa cell projections did not enter it. The subzonal space was wider than that of the control group.Conclusion: Ovarian vitrification and subsequent in vitro growth, in vitro maturation and in vitro fertilization with minimal ultrastructural changes in oocyte could be an alternative to preserve fertility of infertile women.